An Acceptance and Commitment Therapy Smartphone Application for Erectile Dysfunction: A Feasibility Study - Junichi Saito, PhD; Hiroaki Kumano, MD, PhD; Mohammad Ghazizadeh, MD, PhD; Chigusa Shimokawa; Hideki Tanemura (Elsevier, 2023)
ABSTRACT: Background: Erectile dysfunction (ED) is a multifactorial disorder with both psychogenic and organic components, but psychosocial factors are usually neglected. Objective: The purpose of this study was to develop a smartphone application targeting psychosocial factors of ED and to examine its feasibility, acceptability, and treatment response to determine the parameters for a larger clinical trial. Methods: In this single-arm feasibility study, 8 participants with situational ED were enrolled. Dr. App, a newly developed smartphone treatment application for patients with psychogenic ED consisting of 8 weekly modules based on Acceptance and Commitment Therapy, was delivered. The primary outcome was comparison of the International Index of Erectile Function-15 domain scores measured pre- and post-intervention. Results: Six out of 8 participants completed the Dr. App and the post-intervention measures. The Wilcoxon signed-rank test showed a significant change in erectile function (P < 0.05; r = -0.65) and a significant trend in intercourse satisfaction (P < 0.10; r = -0.47) and overall satisfaction (P < .10; r = -0.47). Additionally, the reliable change index values were used to calculate the number of participants for whom a clinically meaningful difference occurred. The results showed that 33.30% of the participants had clinically meaningful differences in erectile function and 66.70% in intercourse satisfaction and overall satisfaction. On the other hand, no significant differences were shown in orgasmic function and sexual desire. Conclusions: Findings from this study support the feasibility, acceptability, and potential usefulness of the smartphone application targeting psychosocial factors of ED and warrant a larger randomized clinical trial to confirm the results.